2018
DOI: 10.3390/ma11071079
|View full text |Cite
|
Sign up to set email alerts
|

Double Feedback Control Method for Determining Early-Age Restrained Creep of Concrete Using a Temperature Stress Testing Machine

Abstract: Early-age restrained creep influences the cracking properties of concrete. However, conventional creep measurements require a large number of tests to predict the restrained creep as it is influenced by the combined effects of variable temperature, creep recovery, and varying compression and tension stresses. In this work, a double feedback control method for temperature stress testing was developed to measure the early-age restrained creep of concrete. The results demonstrate that the conventional single feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…As the above described testing system mainly allows for the effects of restrained linear shrinkage to be examined, the traditional TSTM has been recently modified and improved by numerous researchers, in order to enable thermally insulated and regulated concrete specimens to be examined. These improvements include temperature and humidity control, insulation, simultaneous measurements on restrained and unrestrained specimens, as well as the addition of a closed loop computer‐controlled system 70,82,85,88,113–122 …”
Section: State Of the Art Review Of Longitudinal Testing Devicesmentioning
confidence: 99%
“…As the above described testing system mainly allows for the effects of restrained linear shrinkage to be examined, the traditional TSTM has been recently modified and improved by numerous researchers, in order to enable thermally insulated and regulated concrete specimens to be examined. These improvements include temperature and humidity control, insulation, simultaneous measurements on restrained and unrestrained specimens, as well as the addition of a closed loop computer‐controlled system 70,82,85,88,113–122 …”
Section: State Of the Art Review Of Longitudinal Testing Devicesmentioning
confidence: 99%
“…The specimen would drive the universal joint to move when the specimen length changed with the temperature history. Then the stepping motor would push or pull the universal joint to its original position when the absolute value of the total strain of the restrained specimen exceeded the threshold value [ 17 , 25 , 36 ], as shown in Figure 5 . A compensation cycle is repeated at increments of threshold value to recover the shrinkage strain [ 18 , 31 , 37 ].…”
Section: The Temperature Stress Testmentioning
confidence: 99%
“…Existing studies have shown that the Temperature Stress Testing Machine (TSTM) is a powerful instrument for studying the early-age anti-cracking of concrete under the combined effects of temperature and constraint. TSTMs can accurately control the constraint conditions of the cast-in-place concrete specimens and simulate the tensile damage and cracking process of concrete [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Riding et al [ 31 ] used a rigid cracking frame to measure the uniaxial stress of concrete containing different fly ashes under restrained conditions, and the results showed that fly ashes reduced the cracking risk because of the decrease in the heat of hydration of the cementitious materials.…”
Section: Introductionmentioning
confidence: 99%